Unveiling the implementation of STE(A)M Education: An exploratory case study of Indonesia from experts’ and policymakers’ perspectives - Pasttita Ayu Laksmiwati; Zsolt Lavicza; Adi Nur Cahyono; Wahid Yunianto; Tony Houghton (Cogent Education, 2023)
This study design was an exploratory case study, with semi-structured interviews and document analysis to investigate how STE(A)M education (science, technology, engineering, art, and mathematics) is implemented in Indonesia. The interviews were held with fifteen participants, with practitioners, experts, and policymakers involved. Ninety-nine STE(A)M activities were collected for document analysis, which was analysed through qualitative content analysis. We discovered that STE(A)M implementations in Indonesia focused on research activities, conferences, teacher training, and activities for children and families. These included four implementation stages: initial, growth, expansion, and established stage. The finding pointed out that implementing integrated learning in Indonesia focuses on STE(A)M activities with engineering design processes as the core activities. Moreover, we found that the Indonesian government is providing substantial support to cultivate STE(A)M education by conducting massive teachers’ training and building learning communities among teachers. Therefore, this provides direction for future research to broaden STE(A)M education implementations around the globe by uncovering Indonesian initiatives.